Coming back for more quality learning experience - Saad, Mazni; Husain, Rosita; Nawi, Nafiza Mahyuddin, Wan Nurul Fatimah Wan Mohamad; Mahyuddin, Nafiza (AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK, 2018)
This preliminary study investigates students’ expected learning experiences that determine their return to the same university for further studies. A cross-sectional analysis was done on 190 undergraduate students in a private institution of higher learning. Their opinions were sought regarding the present quality of services offered by the university. Their concern was for quality teaching, lecturers and facilities, and especially course fees, technology, and support systems. The study highlights the need to look again at some of the students’ major complaints, which could guarantee their return to the university’s doorstep.